ETIKA RELIGIUS DAN DAKWAH ISLAM : PERSPEKTIF BEBERAPA SUMBER HUKUM ISLAM - Mustari Mustari (Fakultas Dakwah dan Komunikasi, 2016)
This research discusses about te study of the ethics of religious and Dakwah of Islam from some perspectives of Islam’s law. Then, the objective of this research is to ascertain the study of the ethics of religious and Dakwah of Islam from some perspectives of Islam’s law. The type of the research is a descriptive qualitative done through literatures study. Data collected through documentation, using library research. A sources of the data obtained through primary data and secondary data. The data obtained are then processed with a content analysis method by clarifying the formal object of the research from general to specific. The study’s result represents that the ethics of Dakwah strongly stands up for a freedom of choice because if the God’s will, everybody can be faith all around the world. God provides a freedom of choice as human beings are being equipped the important thing by God that is mind. Indeed, in ethics of Dakwah, Islam people have to salute other people whatever their religions are as humans created by God.